Tree composition of the south-west camly forest area of Lam Vien plateau, Lam Dong province - Chinh, Nguyen Duy; Tiep, Nong Van; Tien, Tran Van (Academia Journal of Biology, 2015)
The south-west Camly forest area is about 12 km on south-west of the Dalat city, at the altitude of 1200 m to 1500 m. There are two main types of forest distributed here: close evergreen forest and clear pine forest. 141 tree species belonging to 89 genera, 44 families of Pinophyta and Magnoliophyta are collected and identified. Of these species, 6 species are listed in the Red Data Book of Vietnam (1996).